On Chinese Contemporary "Crime Drama" and Christian Culture - CHEN, Weihua; QU, Zizheng (Journal of Research for Christianity in China (JRCC), 2023)
As a special type of TV drama, "crime drama" occupies an important position in the current TV drama market in China. Chinese "crime dramas" are more or less influenced by Christian culture in the process of development. The relationship between Chinese contemporary "crime drama" and Christian culture can be seen from the performance of Christian cultural symbols, images and "guilt culture" in Chinese crime dramas.